2013
DOI: 10.1016/j.fertnstert.2012.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fish oil supplementation inhibits formation of endometriosis-associated adhesions in a chimeric mouse model

Abstract: Objective To examine whether dietary fish oil supplementation reduces development of spontaneous endometriosis-associated adhesions using an established model. Design Laboratory-based study. Setting Medical center research laboratory. Patient(s)/Animal(s) Disease-free women of reproductive age and nude mice. Intervention(s) Women were not provided any intervention. Mice were randomized to receive fish oil supplementation or control diet. Main Outcome Measure(s) Experimental endometriosis was establis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 37 publications
(55 reference statements)
1
25
0
Order By: Relevance
“…This finding comes from a 2016 study by Heard et al conducted in mice in which the experimental group was on the diet of 45% of fat and the control group was on a diet of 17% of fat [34]. Another study performed on animals in 2013 by Herington et al seems to confirm the positive influence of fish oils on decreasing the risk of developing endometriosis, demonstrating that supplementation with fish oil reduced the development of postoperative adhesions connected with endometriosis [35].…”
Section: Discussionmentioning
confidence: 95%
“…This finding comes from a 2016 study by Heard et al conducted in mice in which the experimental group was on the diet of 45% of fat and the control group was on a diet of 17% of fat [34]. Another study performed on animals in 2013 by Herington et al seems to confirm the positive influence of fish oils on decreasing the risk of developing endometriosis, demonstrating that supplementation with fish oil reduced the development of postoperative adhesions connected with endometriosis [35].…”
Section: Discussionmentioning
confidence: 95%
“…Interestingly, a recent paper demonstrated the protective effect of fish oil in endometriosis in a chimeric model where human endometrial tissue was injected into the peritoneum of nude mice. 163 Mice administered fish oil exhibited fewer leukocytes within lesions and less collagen deposition at adhesions indicating that dietary intervention may prevent postsurgical adhesion development. These effects may well be due to the formation of pro-resolving lipid mediators such as resolvins and protectins, metabolized from omega 3 fatty acids.…”
Section: Endometriosis: a Complex Disease For Which Improved Treatmenmentioning
confidence: 99%
“…Harrington et al (2013) showed, in their study on mice, that fish oil can be used as an effective adjunctive therapy to reduce post-operative adhesion in endometriosis (10). All 3 studies included in the meta-analysis showed the effect of fish consumption on reducing the disease, however, none were statistically significant (9,11,12).…”
Section: Discussionmentioning
confidence: 99%